Campus Adaptations Vary On Source of College Expense among Engineering Undergraduate Students: Exploring the Relationship Between Campus Adaptations and College Expenses among Engineering Undergraduate Students (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Objective - The study aims to empirically test the relationship between types of campus adaptations and sources of college expenses across engineering undergraduate B. Tech students pursuing a four-year study at Indian Institute of Technology (IIT’s) and National Institute of Technology (NIT’s) in India.Method - The Multivariate Analysis of Variance (Manova) test was run with SPSS vs. 21 to compare the student’s campus adaptations of IIT’s and NIT’s by student’s academic year level. Multistage random sampling with n = 1420 students were selected with parents income (n = 956), bank loan (n =144), government scholarship (n =85), private scholarship (n = 06), loan from private source or money lender for stipulated interest (n = 1) borrowing from relatives (n = 1), income from internship project at institute (n = 1), parents income and bank loan (n = 52) parents income and government scholarship (n =121), parents income, government scholarship and private scholarship (n=09), government scholarship and bank loan (n =16), parents income, government scholarship and bank loan (n =07), parents income and private scholarship (n = 09), parents income, private scholarship and bank loan (n =3), government scholarship, income from internship project (n =1) , parents income and income from internship project (n =2), parents income and donor donation (n =3), parents income and borrowing from relatives (n =7).